2020
DOI: 10.22541/au.159238989.99123083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

QTc prolongation among hydroxychloroquine sulfate-treated COVID-19 patients: An observational study

Abstract: Background: The liberal administration of hydroxychloroquine-sulphate (HCQ) to COVID-19 patients has raised concern regarding the risk of QTc prolongation and cardiac arrhythmias, particularly when prescribed with azithromycin. We evaluated the incidence of QTc prolongation among moderately and severely ill COVID-19 patients treated with HCQ and of the existence of concomitant alternative causes. Methods: All COVID-19 patients treated with HCQ (between Mar 1 and Apr 14, 2020) in a tertiary medical center were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another study in SARS‐CoV‐2 patients reported an increase of 13 (IQR 9–16) ms 41 . Other studies reported QTcF‐prolongation after hydroxychloroquine treatment only in a minority of their cases 43,44 . For example, an average increase of the QTcF‐interval of 1.8% was observed in a cohort of 219 hospitalized and ambulatory SARS‐CoV‐2 patients who were treated with a total dose of 2800 mg hydroxychloroquine, although combined with other antiviral drugs 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in SARS‐CoV‐2 patients reported an increase of 13 (IQR 9–16) ms 41 . Other studies reported QTcF‐prolongation after hydroxychloroquine treatment only in a minority of their cases 43,44 . For example, an average increase of the QTcF‐interval of 1.8% was observed in a cohort of 219 hospitalized and ambulatory SARS‐CoV‐2 patients who were treated with a total dose of 2800 mg hydroxychloroquine, although combined with other antiviral drugs 40 .…”
Section: Discussionmentioning
confidence: 99%
“…40 Another study in SARS-CoV-2 patients reported an increase of 13 (IQR 9-16) ms. 41 Other studies reported QTcFprolongation after hydroxychloroquine treatment only in a minority of their cases. 43,44 For example, an average increase of the QTcF-interval of 1.8% was observed in a cohort of 219 hospitalized and ambulatory SARS-CoV-2 patients who were treated with a total dose of 2800 mg hydroxychloroquine, although combined with other antiviral drugs. 40 In another cohort of 111 hospitalized SARS-CoV-2 patients who were treated with a hydroxychloroquine dose similar to our study (2400 mg), only 5 (7%) of the patients developed a QTcF-prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…In observed observational studies, the outcomes below have been reported. In these studies, it was reported that a percentage of participants received from HCQ had prolonged QTc intervals (Ip et al, 2021;Sogut et al, 2021;Fteiha et al, 2020). In the study by Sogut et al (2021), 91.4% of the participants showed significant improvement, however 13 had adverse events (Sogut et al, 2021).…”
Section: Average Of 65 Yearsmentioning
confidence: 98%